EKSPERIMENTASI MODEL JIGSAW SNOWBALL DRILLING DAN PEER TUTORING SNOWBALL DRILLING PADA MATERI POKOK TABUNG, KERUCUT, DAN BOLA DITINJAU DARI GAYA BELAJAR SISWA - P, Nelly Indriastuti; Kusmayadi, Tri Atmojo; Usodo, Budi (Jurnal Pembelajaran Matematika, 2014)
Abstract: The aims of this research were to determine: (1) which results better mathematics learning achievement between students who were taught by using jigsaw snowball drilling, peer tutoring snowball drilling, or direct instruction, (2) which has better mathematics learning achievement between students with visual learning styles, auditory, or kinesthetic, (3). at each of the learning model, which one has better mathematics learning achievement between student with visual learning style, auditory, or kinesthetic, (4). at each learning style, which one results better mathematics learning achievement between students who were taught by using jigsaw snowball drilling, peer tutoring snowball drilling or direct instruction. This study was a quasi experimental research with 3x3 factorial designs. The population in this study was all students of IX graders of SMPN in Blora in the academic year of 2013/2014. Stratified cluster random sampling was used to select three schools namely SMPN 2 Cepu, SMPN 1 Kedungtuban, and SMPN 1 Cepu. The hypotheses testing used unbalanced two ways ANOVA. Based on the research conducted, it can be concluded as follows. (1) Students who were taught by using jigsaw snowball drilling have better learning achievement than those who were taught by using peer tutoring snowball drilling and direct learning. While the learning achievement of students who were taught by using peer tutoring snowball drilling was better than those who were taught by using direct instruction. (2) Mathematics achievement of auditory students was better than visual and kinesthetic students have. Visual students result mathematics achievement which was better than kinesthetic students. (3) In the jigsaw snowball drilling model, there was no difference in learning achievement in each criterion of studentâs learning styles (visual, auditory, and kinesthetic). In the peer tutoring snowball drilling models, students mathematics achievement which have auditory learning style better than students with visual and kinesthetic learning style; there was no difference in learning achievement between student who have visual and kinesthetic learning styles. In the direct instruction, there was no difference in learning achievement between student who have visual and auditory learning styles; there was no difference in learning achievement between student who have visual and kinesthetic learning styles; and students mathematics achievement which have auditory learning style better than students with kinesthetic learning style. (4) For the students who have visual learning style, jigsaw snowball drilling results better learning achievement than peer tutoring snowball drilling and direct instruction; there was no difference learning achievement in peer tutoring snowball drilling and direct instruction. For the students who have auditory learning style, there was no difference learning achievement in jigsaw snowball drilling and peer tutoring snowball drilling; jigsaw snowball drilling and peer tutoring snowball drilling result better learning achievement than direct instruction. For the students who have kinesthetic learning style, there was no difference learning achievement in peer tutoring snowball drilling and direct instruction. Jigsaw snowball drilling and peer tutoring snowball drilling result better learning achievement than direct instruction.Keywords: Jigsaw Snowball Drilling, Peer Tutoring Snowball Drilling, Direct Instruction, Student Learning Styles, and Mathematics Learning Achievement.